Impact of coal-to-gas transition on individual welfare considering the inverted U-shaped regulation effect of natural gas pipeline accessibility - Shi Jiankui; Xia Yingge; Hu Lun; Zhou Hui; Ma Jiliang; Hu Xiangdong (Scientific Reports)
Abstract Amid the accelerated pace of industrialization and urbanization in China, severe air pollution has emerged as a pressing concern, posing substantial threats to public health and the overall quality of life. Given its pivotal role in the transition towards clean energy, it is of utmost importance to conduct a comprehensive and in-depth assessment of the micro-level impacts of the coal-to-gas transition (CTGT) on individual welfare (IW). This study employs data from the Chinese General Social Survey (CGSS) to scrutinize the effects of the CTGT on IW, and has uncovered three pivotal findings. Firstly, the CTGT significantly enhances IW through a combination of income substitution effect (ISE), capital aggregation effect (CAE), industrial upgrading effect (IUE), and environmental improvement effect(EIE). As a consequence, residents have witnessed significant improvements in their life happiness (LH) and physical health (PH) following the transition. Secondly, natural gas pipelines accessibility (NGPA) has been found to exert an inverted U-shaped regulation influence on the relationship between the CTGT and IW. Thirdly, the welfare-enhancing effects of the CTGT are particularly pronounced among females with lower consumption levels, with a junior high school education or below, and residents in urban areas boasting superior energy supply and infrastructure standards. The findings offer crucial theoretical foundations and policy recommendations for optimizing energy structures and enhancing individual welfare, providing practical guidance for advancing global clean energy transitions and achieving sustainable development goals.